ANALISIS PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TEHADAP KINERJA KARYAWAN PT SUCOFINDO PANGKALPINANG - Tria Lorenza, Meilin; Zamhari; Panjaitan, Fery (Jurnal Progresif Manajemen Bisnis, 2024)
The purpose of this research is to determine the influence of leadership style and work environment on the performance of PT Sucofindo Pangkalpinang employees. This research uses a quantitative research method that uses primary data and secondary data obtained through research questionnaires. The sampling method in this research is by using the Saturated Sampling method (census sampling) for a total of 44 respondents. In this research were employees of PT Sucofindo (Persero) Pangkalpinang. This research uses the Validity Test and Reliability Test to measure validity and reliability, and uses the Classical Assumption Test, Multiple Linear Regression Analysis, Simultaneous Test (F Test), and Partial Test (T Test) and Determination Coefficient (R2) processed with JASP. The research results show (1) Leadership Style has a negative and significant effect on Employee Performance. (2) The work environment has a positive and significant effect on employee. The results of the simultaneous test (F Test) show a significance value of 0.002 < 0.05 and a calculated f value of 7.612 > f table 3.22. This shows that the variables of leadership style and work environment simultaneously influence employee performance.